2022
DOI: 10.3389/fpsyg.2022.929517
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grit in Organizational Performance During a Pandemic

Abstract: In the context of the organizational crisis caused by COVID-19, scholars and professionals have focused on factors that help employees stay at their jobs and perform well. In an uncertain era, grit is a significant employee and organizational sustainability trait. Using 890 responses, this study determined how grit affects organizational performance and used contingencies including supportive climate and transformational leadership as moderators. The hypotheses were tested by examining the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…Te positive relationship between grit and job performance found in the current sample is consistent with the fndings of previous studies on this relationship [18,19,60].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Te positive relationship between grit and job performance found in the current sample is consistent with the fndings of previous studies on this relationship [18,19,60].…”
Section: Discussionsupporting
confidence: 92%
“…It is thought that individuals with high levels of grit are able to make better use of their abilities because they are less distracted by short-term goals and less discouraged by failures and setbacks that are commonly encountered in many performance areas [16], which can lead to better performance in those areas. Numerous empirical studies have demonstrated the positive efect of grit on personal performance in a wide range of felds covering students' academic performance [13,17], employees' job performance [11,18,19], performance in military [20], and sports [21]. In particular, grit has been found to predict both the academic and clinical performance of nursing students after controlling for potential confounders including the year of study and demographic factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these contributions, this study had some limitations. First, although there are reasons why we chose South Korea as the research setting, it is better to have a variety of countries across the globe to increase the generalizability [ 102 , 103 ]; therefore, future studies can examine the impact that this study verifies in different contexts [ 104 ]. Second, the operationalisation of each variable needs to be strengthened because this study used a single item for each variable [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Task performance is one of the most crucial outcomes achieved in the management discipline [ 79 ]. It refers to meeting formal job requirements that follow prescribed work procedures, a type of in-role behavior, and routine administrative work [ 80 ].…”
Section: Moderating Effect Of Organizational Support For Creativitymentioning
confidence: 99%